Anthropogenic debris in three sympatric seal species of the Western Antarctic Peninsula - Julieta D. Cebuhar; Javier Negrete; Lucas S. Rodríguez Pirani; A. Lorena Picone; Maira Proietti; Rosana M. Romano; Carlos O. Della Védova; Ricardo Casaux; Eduardo R. Secchi; Silvina Botta (Science of The Total Environment, 2024)

Modeling and theorizing with agent-based sustainable development - D. Secchi; V. Grimm; D.B. Herath; F. Homberg (Environmental Modelling & Software, 2024)

Feeding habits of South American and sub‐Antarctic fur seals during their nonbreeding season in the southwestern Atlantic Ocean - Renan C. de Lima; Thaise L. de Albernaz; Eduardo R. Secchi; Julieta D. Cebuhar; Silvina Botta (Marine Mammal Science, 2024)
Stomach contents of South American ( Arctocephalus australis ) ( n = 219) (SAFS) and sub‐Antarctic ( A. tropicalis ) ( n = 37) (SFS) fur seals were opportunistically sampled from 1980 to 2021 to examine their feeding habits and resource partitioning in southern Brazil while in their nonreproductive periods. SAFSs mainly consumed abundant coastal pelagic species, such as Anchoa marinii and Doryteuthis sanpaulensis , resulting in high sexual trophic niche overlap. The frequency of occurrence (%FO) of fish prey, especially the overexploited Micropogonias furnieri , decreased between 1980–1992 and 2007–2021, while squid increased. For SFSs, offshore squids such as Ommastrephes bartramii and Illex argentinus were the most important prey considering both sexes in the long‐term. The interspecific trophic niche overlap was low, but it is likely underestimated since it increased with the inclusion of scat samples from SFSs. This sample‐size effect was also observed in Shannon's diversity index, which was lower for underrepresented SFSs. Marine debris ingestion was detected in both species (SAFS %FO = 2.7; SFS %FO = 8.3), with only flexible plastic material found. This study brings novel information on feeding habits of fur seal species in the extreme south of Brazil, as well as unprecedented information about their ecology during the nonreproductive period.

Effects of heat and drought on canola (Brassica napus L.) yield, oil, and protein: A meta-analysis - Mario A. Secchi; Javier A. Fernandez; Michael J. Stamm; Timothy Durrett; P.V. Vara Prasad; Carlos D. Messina; Ignacio A. Ciampitti (Field Crops Research, 2023)

A Synthesis of the Ecology, Human-Related Threats and Conservation Perspectives for the Endangered Franciscana Dolphin - Eduardo R. Secchi; M. J. Cremer; D. Danilewicz; J. Lailson-Brito (Frontiers in Marine Science, 2021)
The franciscana is endemic to subtropical coastal waters of Brazil, Uruguay, and Argentina, and is the only living species of the family Pontoporiidae. It is regarded as the most endangered cetacean in the western South Atlantic. Five management units are recognized (Franciscana Management Areas, FMAs – sensu Secchi et al., 2003a ), with abundance estimates ranging from a few hundred to around 15,000 dolphins. Low reproductive potential and short life span make this species highly susceptible to current non-natural removal rates. Bycatch in gillnet fisheries occurs in high levels since the 1960s in Uruguay and 1980s in Brazil and Argentina. Although other threats exist, such as habitat degradation that includes physical (noise) and chemical pollution, depletion of fish stocks and climate change, incidental mortality in gillnets is currently the greatest threat to franciscanas. Fishing-related mortality ranges from approximately 100, in FMA I, to more than 1,000 in FMA III, and exceed from near two (in FMA IV) to more than five times (in FMA III) the maximum allowed sustainable mortality rate, based on potential biological removal (PBR) approach. These numbers indicate that the species is unlikely to cope with the current levels of bycatch and that urgent and extreme reduction on fishing practice and effort are required to avoid collapse of the franciscana and to lower its risk of extinction. Current mortality levels and projected declines resulted in the listing of the franciscana as “Vulnerable” in the IUCN Red List. Recent fisheries regulations were implemented in areas with extensive bycatch in Brazil and were expected to improve the species’ conservation status. There is evidence, however, that this regulation is insufficient to reduce fishing-related mortality to sustainable levels due to either or both lack of compliance and inadequate regulation strategies. Here we provide a comprehensive review on the franciscana ecology and threats and discuss perspectives for its conservation.

Diverse groups of fungi are associated with plastics in the surface waters of the Western South Atlantic and the Antarctic Peninsula - Ana L. d. F. Lacerda; Maíra C. Proietti; Eduardo R. Secchi; Joe D. Taylor (Molecular Ecology, 2020)
Marine plastic pollution has a range of negative impacts for biota and the colonization of plastics in the marine environment by microorganisms may have significant ecological impacts. However, data on epiplastic organisms, particularly fungi, is still lacking for many ocean regions. To evaluate plastic associated fungi and their geographic distribution, we characterised plastics sampled from surface waters of the western South Atlantic (WSA) and Antarctic Peninsula (AP), using DNA metabarcoding of three molecular markers (ITS2, 18S rRNA V4 and V9 regions). Numerous taxa from eight fungal phyla and a total of 64 orders were detected, including groups that had not yet been described associated with plastics. There was a varied phylogenetic assemblage of predominantly known saprotrophic taxa within the Ascomycota and Basidiomycota. We found a range of marine cosmopolitan genera present on plastics in both locations, i.e., Aspergillus, Cladosporium , Wallemia and a number of taxa unique to each region, as well as a high variation of taxa such as Chytridiomycota and Aphelidomycota between locations. Within these basal fungal groups we identified a number of phylogenetically novel taxa. This is the first description of fungi from the Plastisphere within the Southern Hemisphere, and highlights the need to further investigate the potential impacts of plastic associated fungi on other organisms and marine ecosystems.

Dietary consistency of male South American sea lions (Otaria flavescens) in southern Brazil during three decades inferred from stable isotope analysis - L. Zenteno; E. Crespo; D. Vales; L. Silva; F. Saporiti; L. R. Oliveira; E. R. Secchi; M. Drago; A. Aguilar; L. Cardona (Marine Biology, 2015)

Heterophile Antibodies in Horse Plasma Interfering in an Enzyme-linked Immunosorbent Assay - V. Borromeo; A. Berrini; D. Gaggioli; C. Secchi (Veterinary Research Communications, 2007)